Validation Short Food Literacy Questionnaire for Women: Translation and Cultural Adaptation in Indonesia - Haikal, Haikal; Suhito, Hanif Pandu; V.Duong, Tuyen; A. Utami, Fasty; Setiono, Oki; Puspita, Fitria Dewi; Rachmani, Enny (Health Science UDINUS, 2024)
Food literacy is vital for public health, particularly in urban areas, as it enhances understanding of nutrition and fosters healthy eating patterns. This study aims to adapt and validate the SFLQ instrument for the Indonesian population, especially women. This study distributed the questionnaire to 968 respondents from across 16 sub-districts in Semarang City. This study validated SFLQ and modified it to fit Indonesia’s condition. The 12-item questionnaire scored on a 4-point Likert scale, evaluates basic knowledge, understanding, and ability to assess nutritional information. Confirmatory Factor Analysis (CFA) determined the instrument's structure, followed by Structural Equation Modeling (SEM) for validation. Construct validity was tested by correlating SFLQ scores with health literacy, gender, and education, while internal consistency was assessed using Cronbach's Alpha. The study revealed a unidimensional structure, high internal consistency (Cronbach's Alpha = 0.891), significant factor loadings (0.400–0.730), and a strong correlation between nutritional and health literacy (rs = 0.606, p < 0.01). Construct validity was supported by a significant positive correlation between food literacy and health literacy scores (rs = 0.606, p < 0.01). The Jonckheere-Terpstra test also showed a trend of increasing nutritional literacy scores with higher health literacy categories (p = 0.000)—significant correlations with education level and health literacy supported validity. Aspects like dietary impact evaluation showed room for improvement